(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzes the lifestyle of the protagonists in Khurshid Dostmuhammad’s story "View", the process of self-awareness, the writer’s skill in depicting his sister, brother, tenant, relationship with people in the office, and the modernist coverage of psychospiritual images.